Faktor-faktor yang Mempengaruhi Kejadian Stunting pada Anak Balita di Wilayah Pedesaan dan Perkotaan (The Factors Affecting Stunting on Toddlers in Rural and Urban Areas) - Farah Okky Aridiyah; Ninna Rohmawati; Mury Ririanty (Pustaka Kesehatan, 2015)
In 2013, the prevalence of stunting in rural areas of Jember is 67% and 27,27% for urban areas. Stunting if problem above 20% that is a public health problem. The purpose of this study was to analyze the factors that influence the genesis of stunting in toddlers between rural and urban areas. This type of this study is an observasional analytic with cross-sectional approached and conducted in Patrang health center and Mangli health center for urban whereas Kalisat health centers for rural with sample fifty respondents each. Analysis of data consisting of chi-square test, mann whitney test and logistic regression with α=0,05. Result of analysis showed that affecting factors of stunting occurrence in toddlers who are in the rural and urban areas were the mother's education, family income, mother's knowledge of nutrition, exclusive breastfeeding, complementary feeding age provision, zinc and iron adequacy level, infection disease history and genetic factors. However, another factors such as mother's work, family numbers, immunization status, energy adequacy level and BBLR status didn't affect the occurrence of stunting. Protein and calcium adequacy level in rural areas showed a significant relation while in urban areas showed no relation. The most factor affecting stunting on toddlers in rural and urban areas was zinc adequacy level. Keyword: Stunting, Toddlers, Rural, Urban